Mental Events Changes of Mind in European Narratives from the Middle Ages to Postrealism - Schmid, Wolf (Hamburg University Press, 2021)
Mental events, changes that take place in the consciousness of the narrated characters or the narrating entity, are an essential theme of narrative works. This book first undertakes a typologization of the procedures by means of which the content of consciousness is represented, as well as outlining the conditions of events and the criteria of eventfulness. Then, classic narrative works from various cultures and epochs - from Parzival and Tristan, through Samuel Richardson and Jane Austen, to Fëdor Dostoevskij and Anton Čexov - are examined in terms of how mental events are shaped in them. The book follows three guiding questions. What philosophy of events and consciousness is expressed in the works? How disposed are different cultures and epochs to eventfulness? To what extent do they allow for the presentation of fundamental mental changes?